Sattvavajaya Chikitsa: Need of Today’s Era - Pallavi Bharti; Vijay Shankar Pandey (AYUSHDHARA, 2023)
Speed, accuracy and over ambitiousness are the prime demands of today’s metaphysical society. People can’t even pay attention to their physical and mental health. Irregular food habits, suppression of natural urges, insomnia are becoming the part and parcel of today’s life, giving rise to psychosomatic disorders. Ayurveda, the ancient system of Indian medicine evolved through millennium contains clear potentials of the modern understanding of natural science. Inspire of its historically inevitable beginnings, the science took in the ancient period itself the momentous step from the magic-religious therapeutics to rational therapeutics i.e., in the terminology of physicians themselves from Daivavyapashraya Chikitsa to Sattvavajaya Chikitsa. Ayurveda has considered the mental and physical diseases as two separate specialized subjects in certain contexts. However, no line of demarcation has been drawn between the physical and mental diseases and a flexible psychosomatic approach has been put forward. Ayurveda emphasizes its treatment modalities into three Chikitsa viz., Sattvavajaya Chikitsa, Yuktivyapashraya and Daivavyapashraya Chikitsa. Sattvavajaya is the mental restraint, or a “mind control” as referred by Charaka, is achieved through “spiritual knowledge, philosophy, fortitude, remembrance, and concentration. Health regimens as (Swasthvritta), good conduct (Sadvritta), and yoga acts as a traditional mental health promoting practices.